Analisis Preferensi dan Kepuasan Konsumen terhadap Beras di Kecamatan Mulyorejo Surabaya Jawa Timur (The Analysis of Preferences and Customer Satisfaction on Rice in Mulyorejo District, Surabaya, East Java) - Rita Nurmalina; Endang Pudji Astuti (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2011)
Rice is a very important commodity. Rice plays an important role in food security, economic stability, and employment. Consumer behavior in rice consumption continues to grow. Improved incomes lead to increased demands on quality. Changes in demographic structures, such as level of education, lifestyle, technology, transportation, and communication, affect the customer preferences and satisfaction with the rice they consume. In line with efforts to increase productivity, the rice should be produced to meet consumer expectations which are constantly evolving.  This study aimed to identify the characteristics, analyze the decision-making process, preferences, and customer satisfaction, as well as making the right marketing mix recommendations based on the study of consumer behavior on three different social classes (lower class, middle, and upper). Convinience Sampling was used. The analytical tool used in this study was a descriptive analysis, Important & Performance Analysis (IPA) and the Customer Satisfaction Index (CSI).  Data processing with descriptive analysis showed some differences in the characteristics of responders and decision-making processes at all three social classes. The differences associated with educational level and family income levels, initial consideration of the purchase of rice, and where to purchase the rice.  CSI showed that the total satisfaction on all three social classes is entirely in the range “satisfied”. However, the higher the social class, the higher the satisfaction of the rice consumed. Data processing by IPA showed that the performance, which should be improved based on consumer preference and satisfaction, was a top-class ease of getting rice and seller services. The performance on middle-class consumers have to be improved in assessing durability of rice, grain uniformity, and broken. While the upscale consumer should improve performance in terms of price, flavor, broken, and clean rice.Keywords: consumption, quality, expectation, social class, sample, performance.